Effectiveness of track stiffness reduction in attenuation of metro induced vibrations received by historical buildings - Sadeghi,J. (2018)
Abstract Preservation of historical buildings is a main challenge in civil engineering field. One of the main concerns in this regard is metro induced vibration received by historical structures. There is a need to evaluate effectiveness of vibration mitigation measures in preservation of monumental buildings. The most widely used method of reducing metro vibrations is changes in the structure of the vibration source (not sufficiently investigated in the literature). In response to this need, effectiveness of track stiffness reduction in mitigation of vibration was investigated in this research. Comprehensive field tests were conducted in the Iranian metro lines. The track stiffness as well as the induced vibrations were measured. It was shown that track stiffness has noticeable role in the track levels of vibration, and in turn in metro vibration reduction. The amounts of vibration reduction were derived as a function of track stiffness reduction.